Production of platform chemicals from sustainable resources - Fang, Zhen; Smith, Richard L.; Qi, Xinhua (Biofuels and biorefineries, 2017)
This book provides state-of-the-art reviews, the latest research, prospects and challenges of the production of platform chemicals such as C6 sugars, 5-hydroxymethylfurfural, furfural, gamma-valerolactone, xylitol, 2,5-furandicarboxylic acid, levulinic acid, ethanol and others from sustainable biomass resources using processes that include heterogeneous catalysis, ionic liquids, hydrothermal/solvothermal, electrochemical and fermentation methods. It also discusses the application of these chemicals and their derivatives for synthesizing commodity chemicals via various routes. Intended as a reference resource for researchers, academicians and industrialists in the area of energy, chemical engineering and biomass conversion, it provides a wealth of information essential for assessing the production and application of various biomass-derived platform chemicals using biological, chemical and electrochemical techniques.